1991
DOI: 10.1126/science.1887217
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Inflammatory Arthropathy Resembling Rheumatoid Arthritis in Mice Transgenic for HTLV-I

Abstract: Human T cell leukemia virus type-I (HTLV-I) is the etiologic agent of adult T cell leukemia and has also been suggested to be involved in other diseases such as chronic arthritis or myelopathy. To elucidate pathological roles of the virus in disease, transgenic mice were produced that carry the HTLV-I genome. At 2 to 3 months of age, many of the mice developed chronic arthritis resembling rheumatoid arthritis. Synovial and periarticular inflammation with articular erosion caused by invasion of granulation tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
149
0
3

Year Published

1996
1996
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(161 citation statements)
references
References 27 publications
(15 reference statements)
7
149
0
3
Order By: Relevance
“…IL-1␣ Ϫ/Ϫ , IL-1␤ Ϫ/Ϫ , and IL-1␣/␤ Ϫ/Ϫ mice were generated as previously described (7). HTLV-I Tg mice, originally produced by injecting the LTR-env-pX-LTR region of the HTLV-I genome into a (C3H/HeN ϫ C57BL/6J)F 1 ovum (18), were backcrossed to BALB/cA mice (Clea, Tokyo, Japan) for 12 generations and then were used for the experiments. These mice start to develop arthritis spontaneously at 4 534 SAIJO ET AL weeks of age, and 60% and 80% of the mice are affected at 3 months and 6 months of age, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…IL-1␣ Ϫ/Ϫ , IL-1␤ Ϫ/Ϫ , and IL-1␣/␤ Ϫ/Ϫ mice were generated as previously described (7). HTLV-I Tg mice, originally produced by injecting the LTR-env-pX-LTR region of the HTLV-I genome into a (C3H/HeN ϫ C57BL/6J)F 1 ovum (18), were backcrossed to BALB/cA mice (Clea, Tokyo, Japan) for 12 generations and then were used for the experiments. These mice start to develop arthritis spontaneously at 4 534 SAIJO ET AL weeks of age, and 60% and 80% of the mice are affected at 3 months and 6 months of age, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Development of arthritis was then compared between homozygous-deficient mice and wild-type littermates. The pX transgene was detected by dot-blot hybridization of the tail DNA (18).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] We previously established mice carrying human T cell leukemia virus type 1 (HTLV-1) representing one of the most suitable animal models of human RA. 13 Using this model, we have recently demonstrated that intra-articular administration of anti-Fas MAb improved the paw swelling and histological features of arthritis by induction of apoptosis of both synoviocytes and mononuclear cells in the inflamed synovium. 14 These findings clearly suggest that apoptosis via the Fas/FasL system may be an important factor for regression of proliferative rheumatoid synovium and administration of anti-Fas MAb could be a novel therapeutic strategy for RA.…”
Section: Introductionmentioning
confidence: 96%
“…The oncogenic properties of this protein have been established by various assays, including transformation of primary T lymphocytes (Grassmann et al, 1989), cooperation with Ras in transformation of ®broblasts (Pozzatti et al, 1990) and induction of tumours in transgenic mice (Nerenberg et al, 1987;Benvenisty et al, 1992;Grossman et al, 1995). Tax transgenic mice are also known to develop several pathologies including thymus atrophy (Furuta et al, 1989), muscle degeneracy (Nerenberg and Wiley, 1989), arthritis (Iwakura et al, 1991) and a proliferation of ductal cells of the salivary gland resembling the SjoÈ gren syndrome (Green et al, 1989). These disorders correlate with observations made in HTLV-1-infected patients (Ozden et al, 1996).…”
Section: Introductionmentioning
confidence: 99%